Problematyka praw zwierząt w dyskursie publicznym w Polsce - Morye, Igor (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Concern for the fate of animals in dependence on humans was first expressed in a statute in the 19th century in Great Britain. In Poland, penalties for animal abuse appeared almost a hundred years later, in a regulation of the President of the Republic of Poland in 1928. We have evolved from the times of vivisection, when Descartes argued that an animal is a kind of machine and has no feelings, to the present day, in which we surround domesticated animals with care and treat them with understanding.
Keywords: prawa zwierząt; dobrostan zwierząt; hodowla zwierząt; ubój rytualny; ochrona środowiska; wyzwolenie zwierząt; Światowa Deklaracja Praw Zwierząt; Trybunał Konstytucyjny; partie polityczne; władza; ustawa; Unia Europejska; animal rights; animal welfare; animal breeding; ritual slaughter; environmental protection; animal liberation; World Declaration of Animal Rights; Constitutional Court; political party; power; law; European Union